Cost-effective strategies to knock down genes of interest in the retinas of adult zebrafish - Shihabeddin, Eyad; Santhanam, Abirami; Aronowitz, Alexandra L.; O’Brien, John (Frontiers in Cellular Neuroscience, 2024)
High throughput sequencing has generated an enormous amount of information about the genes expressed in various cell types and tissues throughout the body, and about how gene expression changes over time and in diseased conditions. This knowledge has made targeted gene knockdowns an important tool in screening and identifying the roles of genes that are differentially expressed among specific cells of interest. While many approaches are available and optimized in mammalian models, there are still several limitations in the zebrafish model. In this paper, we describe 2 approaches to target specific genes in the retina for knockdown: cell-penetrating, translation-blocking Vivomorpholino oligonucleotides and commercially available lipid nanoparticle reagents to deliver siRNA. We targeted expression of the PCNA gene in the retina of a P23H rhodopsin transgenic zebrafish model, in which rapidly proliferating progenitor cells replace degenerated rod photoreceptors. Retinas collected 48 hours after intravitreal injections in adult zebrafish reveal that both Vivo-morpholinos and lipid encapsulated siRNAs were able to successfully knock down expression of PCNA. However, only retinas injected with Vivo-morpholinos showed a significant decrease in the formation of P23H rhodopsin-expressing rods, a downstream effect of PCNA inhibition. Surprisingly, Vivo-morpholinos were able to exit the injected eye and enter the contralateral non-injected eye to inhibit PCNA expression. In this paper we describe the techniques, concentrations, and considerations we found necessary to successfully target and inhibit genes through Vivo-morpholinos and lipid encapsulated siRNAs.